Potret Dakwah di Kelurahan Batu Gadang Kecamatan Lubuk Kilangan Kota Padang - Jusmanizar, Fajrina Margareth Viruliana (Mediakita, 2022)
This research is a descriptive qualitative research, researchers are trying to collect and collect data on proselytizing activities that occur in Batu Gadang Village. The data collection technique used by the researchers in this study is an observation technique, namely visiting the location directly and seeing how the proselytizing process was carried out in Batu Gadang Village. Researchers also use several book sources related to problems in the field. The results of this study reveal that: 1) Da'wah in Batu Gadang is still running as usual, but there is no rapid development so that the da'wah is also in demand by young people, not only the elderly. 2) People in Batu Gadang prefer da'i who come from outside the Batu Gadang wilayang, because the proselytizing they convey is not monotonous and not bored. Da'wah that is often used is proselytizing through face-to-face or lectures with material on akidah, akhlak, fiqh and mua'amalah. 3) There are several institutions or organizations that can help the development of proselytizing in Batu Gadang, namely TPQ, MDTA and Majlis Ta'lim.